Direitos humanos em aulas de História: propostas didáticas de promoção de cidadania em uma escola do Agreste de Alagoas (2020-2023) - Silva, Midiane Cordeiro da (2023)
This research seeks to demonstrate how human rights can enhance the history classes in the process of training for citizenship. We seek from thematic clippings enable new views on issues that permeate the daily lives our four students. The didactic experiences that resulted in the preparation of a textbook for history teachers were applied in the elementary school Crispiano Ferreira de Brito, in the municipality of Arapiraca – AL, in order to reinforce the promotion of human rights and citizenship in history classes. The proposals presented seek to fortify and implement the general humanities competencies in the national core curriculum (BNCC) and enhance the foundations of human rights education provided int the National Plan for Human Rights Education (PNEDH). The studies presented have the perspective of enabling the construction of didactic proposals that take significant historical knowledge in the face of the demands of the time lived, and so enabling readings of the world determined by the tools that historical studies offer.